Síndrome da apnéia obstrutiva do sono: prevalência e variáveis associadas em pacientes portadores de hipertensão arterial resistente e refratária - Silva, Darley Paulo Fernandes da (2024)
Introduction: Obstructive sleep apnea-hypopnea syndrome (OSAHS) is a highly prevalent sleep-disordered breathing observed in around 15% to 25% of the world's adult population. It is considered an important cause of resistant arterial hypertension and secondary refractory arterial hypertension. Casuistic and Methods: This is a retrospective study of 200 adult participants diagnosed with hypertension (including patients with controlled resistant hypertension, resistant hypertension, and refractory hypertension). Results: In our study, the prevalence of OSAHS in patients with resistant and refractory hypertension is 33% and 29%, respectively, in the Mild form and 64% and 62%, respectively, in the Moderate/Severe form. In the sample studied, there is a predominance of females in all categories of OSAHS. A quarter of patients with a previous heart presented refractory hypertension. Patients with moderate/severe forms of OSAHS have less effective sleep; patients with resistant hypertension and refractory hypertension have higher blood pressure and heart rate during sleep in comparison to other non-resistant hypertensive patients. Patients with Moderate/Severe forms of OSAHS have a greater association with Diabetes Mellitus; there is an association between Dyslipidemia, Diabetes and previous Cerebrovascular Accident (CVA) with resistant hypertension; patients classified as resistant and refractory hypertensive have greater glycemic and renal function alterations. Conclusions: In our study, the prevalence of OSAHS was higher in the Moderate/Severe forms. There is a predominance of females, but the ratio between women and men changes as the severity of OSAHS increases. This proportion decreases as the severity of OSAHS increases. There is an association between refractory hypertension and previous heart attacks. OSAHS not only interferes with sleep quality, but also worsens cardiac and cerebral vascular risk factors. Since OSAHS is a highly prevalent respiratory disorder in the world's adult population, there is an urgent need to understand its pathophysiological mechanisms and its relationship with resistant and refractory forms of hypertension.